Does patient age influence procedural management of kidney trauma? - Nizar Hakam; Behzad Abbasi; Umar Ghaffar; Kevin D. Li; Hiren Patel; Charles P. Jones; Joseph Cuschieri; Benjamin N. Breyer (BMC Urology)
Abstract Objectives We aimed to examine the association between patient age and procedural intervention, especially nephrectomy, in patients with renal trauma in the National Trauma Data Bank (NTDB). Materials and methods We queried the 2013–2020 NTDB for adult renal trauma patients with an American Association for the Surgery of Trauma (AAST) grade. Patients without AAST grade or with no sign of life were excluded. We constructed a multinomial logistic regression model to demonstrate the association between age and procedural interventions (renal angioembolization, renorrhaphy and nephrectomy). Models were adjusted for patient, hospital, and clinical factors. Results Our cohort was comprised of 49,884 patients with renal trauma aged 18–89 years, of which 691 (1.4%), 995 (1.9%), and 3,366 (6.8%) underwent angioembolization, renorrhaphy, and nephrectomy, respectively. After adjusting for relevant variables, the risks of nephrectomy and angioembolization were positively associated with patient age, particularly in those 40 years of age and older. Adjusted risk of nephrectomy (OR 0.07 per 10 years of age, 95% CI 0.03–0.11, p < 0.001) and angioembolization (OR 0.19 per 10 years of age, 95% CI 0.14–0.24, p < 0.001) ranged between ≈ 0.6% and ≈ 1%, and between ≈ 0.3% and ≈ 1% across the patient age range, respectively. Plots depicting marginal effect of age is demonstrated that in patients above 35–40 years of age, a 1-year increase in age is associated with a progressively higher increase in risk of both nephrectomy and angioembolization. The adjusted risk of Renorrhaphy (OR -0.003 per 10 years of age, 95% CI -0.06-0.06, p = 0.92) did not vary substantially with age and the marginal effect of age was negligible across all ages. Conclusions Older patients with renal trauma are more likely to receive procedural intervention namely nephrectomy and renal angioembolization. These results suggest possible age-related cognitive bias in renal trauma management.